2002
DOI: 10.1590/s0100-879x2002000600002
|View full text |Cite
|
Sign up to set email alerts
|

Somaclonal variation: a morphogenetic and biochemical analysis of Mandevilla velutina cultured cells

Abstract: Cell cultures of Mandevilla velutina have proved to be an interesting production system for biomass and secondary metabolites able to inhibit the hypotensive activity of bradykinin, a nonapeptide generated in plasma during tissue trauma. The crude ethyl acetate extract of cultured cells contains about 31-to 79-fold more potent anti-bradykinin compounds (e.g., velutinol A) than that obtained with equivalent extracts of tubers. Somaclonal variation may be an explanation for the wide range of inhibitor activity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In which, early stages of culture the clumped cells showed round cells, while elongated in later stages (Fig. 3a-c), such results were observed by Maraschin et al (2002) in Mandevilla velutina cell culture and reported that the meristematic cells showed typical round shape in initial growth phases, whereas elongated cells in exponential phases. Cell biomass was influenced by the different concentrations of plant growth regulators in suspension culture.…”
Section: Resultssupporting
confidence: 75%
“…In which, early stages of culture the clumped cells showed round cells, while elongated in later stages (Fig. 3a-c), such results were observed by Maraschin et al (2002) in Mandevilla velutina cell culture and reported that the meristematic cells showed typical round shape in initial growth phases, whereas elongated cells in exponential phases. Cell biomass was influenced by the different concentrations of plant growth regulators in suspension culture.…”
Section: Resultssupporting
confidence: 75%
“…Preliminary studies of TCIV showed its linkage with GPRE ( Bednarek et al, 2021a ). Moreover, the two phenomena’ origin might be based on biochemical processes ( Maraschin et al, 2002 ; Kumari et al, 2009 ; Makowska and Oleszczuk, 2014 ). It was suggested that the callose interstitial layer in microspores might be necessary for new plant regeneration efficiency ( Rivas-Sendra et al, 2019 ; Dubas et al, 2021 ; Zieliński et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%